Frequency and Relevance of Thyroid Dysfunction in Patients with Chronic Heart Failure: A Cross Sectional Study at Yaoundé Central Hospital, Cameroon - Honoré, Kemnang Yemele; Moor, Vicky J Ama; Kuate, Liliane Mfeukeu; Martine, Etoa; Daryl, Tcheutchoua Nzokou; Agoons, Batakeh B; Samba, Esther Mbono; Amazia, Falmata; Gaelle, Nangue Tiogoung; Ossongo (Archives of Clinical and Biomedical Research, 2021)
Background: Abnormalities of thyroid function have been reported in patients with heart failure (HF). We aimed to evaluate the frequency and clinical relevance of dysthyroidism in Cameroonians with HF. Methods: This was a cross-sectional study from January to May 2020. Including consenting adults followed up at the Yaoundé Central hospital for HF. We assessed serum level of TSH, free T3 and free T4 using ELISA method. We sought for associations between thyroid hormones levels and HF-related variables using Pearson and Spearman correlations tests. The threshold of significance was set at 0.05. Results: 63 participants were included (33males) with a mean age of 62 ±14 years. Among them, 33 (52%) were hypertensive, 16 (25.4%) had atrial fibrillation, and half (52%) had stage II HF according to the New-York Heart Association. Dysthyroidism was found in 25 subjects (39.6%), with 17 (26.9%) and 6 (9.5%) cases of low-T3 syndrome, and subclinical hyperthyroidism respectively. TSH levels were weakly but significantly correlated with the stage of HF (r=0.31, p=0.01) and slightly correlated with left ventricular ejection fraction (LVEF) (r=-0.31, p=0.01). Free T3 levels were weakly but significantly correlated with the number of hospitalizations over the last 12 months (r=-0.36, p<0.01), and the LVEF (r=0.28, p=0.02). Conclusion: Dysthyroidism affects nearly two out of five patients suffering from heart failure in our sample. It could be associated with a more severe clinical presentation. More studies need to be done to assess the long-term prognosis in sub-Saharan African populations with HF and dysthyroidism.